2013
DOI: 10.3389/fnint.2013.00105
|View full text |Cite
|
Sign up to set email alerts
|

BK channel β1 and β4 auxiliary subunits exert opposite influences on escalated ethanol drinking in dependent mice

Abstract: Large conductance calcium-activated potassium (BK) channels play a key role in the control of neuronal activity. Ethanol is a potent activator of BK channel gating, but how this action may impact ethanol drinking still remains poorly understood. Auxiliary β subunits are known to modulate ethanol-induced potentiation of BK currents. In the present study, we investigated whether BK β1 and β4 subunits influence voluntary ethanol consumption using knockout (KO) mice. In a first experiment, mice were first subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 35 publications
3
46
0
Order By: Relevance
“…It is noteworthy that GIRK3 deletion did not alter ethanol consumption under a continuous schedule of access or in the later part of a 4-h session. This finding points to a selective effect on drinking activity associated with intoxication (as defined by a BAL >80 mg/dL), given that continuous access to ethanol leads to sporadic bouts of drinking and produces only brief peaks of intoxication (29,30), whereas limited access leads to binging and produces BALs that positively correlate with intake in C57BL/6J mice (31)(32)(33). Furthermore, the effect of GIRK3 deletion on binge-like drinking could be reversed by virally mediated expression of GIRK3 in the VTA, and was associated with a blunted response of the mesolimbic DA pathway to ethanol, as demonstrated by ethanolinduced excitation of VTA neurons and DA release in the NAc.…”
Section: Girk3 Deletion Prevents Ethanol-induced Release Of Da In Thementioning
confidence: 99%
“…It is noteworthy that GIRK3 deletion did not alter ethanol consumption under a continuous schedule of access or in the later part of a 4-h session. This finding points to a selective effect on drinking activity associated with intoxication (as defined by a BAL >80 mg/dL), given that continuous access to ethanol leads to sporadic bouts of drinking and produces only brief peaks of intoxication (29,30), whereas limited access leads to binging and produces BALs that positively correlate with intake in C57BL/6J mice (31)(32)(33). Furthermore, the effect of GIRK3 deletion on binge-like drinking could be reversed by virally mediated expression of GIRK3 in the VTA, and was associated with a blunted response of the mesolimbic DA pathway to ethanol, as demonstrated by ethanolinduced excitation of VTA neurons and DA release in the NAc.…”
Section: Girk3 Deletion Prevents Ethanol-induced Release Of Da In Thementioning
confidence: 99%
“…sensitive and -insensitive components of related ion channels (Mihic et al, 1997;Liu et al, 2003Liu et al, , 2013. While these conventional approaches are powerful and have proved successful, they cannot easily determine whether the mutations identified as important for ethanol effects in vitro are also relevant to ethanolmodulated behaviors in vivo.…”
Section: The Human Bk Channel Can Functionally Replace the C Elegansmentioning
confidence: 99%
“…In a chimericbased in vitro approach, the T352 residue would not be targeted, and as a result never identified. Liu et al (2013) demonstrated the importance of the intracellular portion of the BK channel, and Liu et al (2008) found that mutation of calcium-binding residues in the Ca 2ϩ bowl and RCK1 domain abolished the ability of ethanol to activate the BK channel in vitro. However, mutations of the calcium-binding residues also dramatically alter calcium dependence and greatly re- .23).…”
Section: The Human Bk Channel Can Functionally Replace the C Elegansmentioning
confidence: 99%
See 2 more Smart Citations